Pembangunan Sistem Informasi Praktik Kerja Industri (Prakerin) berbasis Website menggunakan Model Pengembangan Perangkat Lunak Waterfall Studi Kasus : SMK Plus Almaarif Singosari - Gede Jaya Widhi Aryadi; Ahmad Afif Supianto; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
SMK Plus Almaarif Singosari annually doing industrial internship. There are still problems in the internship activity. The problem is about delivery of information that is still manual because it is only conveyed through meetings with parents. This makes the information to be received by students can be limited, inaccurate or not delivered. The limited information received by students such as requirements, industries that are suitable to be used as workplaces and positions and occupations in the industry. Based on problems related to the management of internship, it is needed a system that can manage information about the internship and can minimize existing problems. The system to be built is based on a website using the Laravel framework. In developing the information system, a waterfall software development model is used. The result from this research are 3 as-is business process modeling, 3 to-be business process modeling,4 actor, 15 user requirements, 32 functional requirements, and 1 non-functional requirement, 1 architectural design modeling, 32 sequence diagrams, 3 class diagrams, 1 physical data model and 11 sample design interfaces. The results of the requirements analysis are approved by the user, proven by the results of User Acceptance Testing (UAT). Unit testing explains that the existing function yields a valid percentage of 100%.